PENGARUH TERAPI MUSIK MOZART DALAM MENGURANGI DISMENOREA PRIMER PADA REMAJA PUTRII - Sumi; Marleni; Ayudita (JURNAL SMART ANKes, 2024)
Adolescence is a period between the ages of 12-21, marking the transition from childhood to adulthood, which in females is often characterized by dysmenorrhea. Primary dysmenorrhea can occur due to an increase in prostaglandins, causing uterine muscles to contract, leading to cramps in the lower abdomen, back, and legs. Dysmenorrhea pain can be managed through pharmacological and non-pharmacological therapies, such as Mozart classical music therapy. Mozart classical music has positive effects on health and those who listen to it. With a duration of 15-20 minutes, the Mozart classical music piece Sonata in D for Two Pianos, K. 448, with a tempo of 60-80 beats per minute, can help listeners relax. Its harmonized rhythms generate alpha and beta waves in the eardrum, providing a calming and relaxing effect, potentially reducing pain and promoting relaxation. The study was conducted at SMA Negeri 2 Mendo Barat with 33 respondents. This research employed a pre-experimental method with a one-group pre-test and post-test design. Before the Mozart classical music therapy was administered, most respondents experienced moderate dysmenorrhea with pain levels of 4, 5, and 6. The study results showed that after two sessions of Mozart classical music therapy, each lasting 15 minutes over two days, the average pain level of the respondents decreased to levels 1 and 2. This indicates that Mozart classical music therapy can reduce primary dysmenorrhea in adolescent girl.